OP0139 FUNCTIONAL EVALUATION OF THE SJÖGREN'S SYNDROME AND SYSTEMIC LUPUS ERYTHEMATOSUS DDX6-CXCR5 RISK INTERVAL. (2nd June 2020) - Wiley, M. M.; Khatri, B.; Tessneer, K. L.; Joachims, M. L.; Stolarczyk, A. M.; Rasmussen, A.; Bowman, S. J.; Radfar, L.; Omdal, R.; Wahren-Herlenius, M.; Warner, B. M.; Witte, T.; et al.
Abstract : Background: Sjögren's Syndrome (SS) and Systemic Lupus Erythematosus (SLE) are distinct chronic, complex autoimmune diseases with shared characteristics such as autoantibodies, heightened interferons, and polyarthritis. SS and SLE genome-wide association studies (GWAS) report strong associations with the DDX6-CXCR5 risk interval. DDX6 suppresses interferon stimulated gene expression and CXCR5 regulates T cell functions implicated in autoimmunity. Objectives: To identify functional variants that impact regulation in the DDX6-CXCR5 interval. Methods: Fine-mapping was done using ImmunoChip data from 3785 SLE, 1916 SS cases and 6893 population controls of European ancestry that were imputed and tested for SNP-trait association. Bayesian statistics assigned posterior probabilities to SNPs and defined a credible set of risk variants. Bioinformatic analyses further prioritized variants with predicted functionality. Electrophoretic mobility shift assays (EMSAs) and luciferase expression were used to validate predicted SNPs in EBV transformed B (EBV B) cells. Results: While some differences were observed, the overall SS and SLE association signals were similar. SNP-SS rs9736016 near CXCR5 and SNP-SLE rs76409436 near DDX6 were the most significant but did not show evidence of functionality. Bayesian statistics defined credible sets of variants in strong D' in common between both SS and SLE. Bioinformatics analyses (Haploreg, RegulomeDB, ENCODE data, etc) further refined the credible set and identified 5 common SNPs with strong evidence of functionality in immune cell types: rs4938572, rs4936443, rs57494551, rs7117261 and rs4938573. EMSAs showed a significant increase in protein binding to the risk allele of rs57494551 (p=0.0001), rs7117261 (p=0.0001) and rs4938573 (p=0.0003), but not the others, using nuclear lysates from EBV B cells. Luciferase vectors with a minimal promoter or no promoter were used to test for enhancer or promoter activity, respectively. To this end, the rs57494551 risk allele exhibited a significant increase in enhancer activity (p=0.0001). In contrast, the rs7117261 risk allele decreased enhancer activity (p=0.018). The rs4938573 risk allele decreased enhancer (p=0.043) and promoter (p=0.024) activity. While rs7117261 or rs4938573 were not reported in eQTL databases, GTex data reported rs57494551 as an eQTL that alters DDX6 expression in whole blood (p=1.8E-7). Additionally, these functional SNPs have been associated with looping events to several proximal promoters in nearby genes in immune cells. Conclusion: SS and SLE have similar genomic architecture across the DDX6-CXCR5 risk interval. Multiple variants in the credible set exhibited allele specific changes in protein binding, as well as modified enhancer activity, promoter activity or both. Ongoing studies will use Cas9 in EBV B cells to determine which other loci are within the local regulatory network. Disclosure of Interests: Mandi M Wiley: None declared, Bhuwan Khatri: None declared, Kandice L Tessneer: None declared, Michelle L Joachims: None declared, Anna M Stolarczyk: None declared, Astrid Rasmussen Speakers bureau: Novartis, ThermoFischer, Simon J. Bowman Consultant of: Astrazeneca, Biogen, BMS, Celgene, Medimmune, MTPharma, Novartis, Ono, UCB, xtlbio, Glapagos, Speakers bureau: Novartis, Lida Radfar: None declared, Roald Omdal: None declared, Marie Wahren-Herlenius: None declared, Blake M Warner: None declared, Torsten Witte: None declared, Roland Jonsson: None declared, Maureen Rischmueller: None declared, Patrick M Gaffney: None declared, Judith A. James Grant/research support from: Progentec Diagnostics, Inc, Consultant of: Abbvie, Novartis, Jannsen, Lars Ronnblom Grant/research support from: AZ, Speakers bureau: AZ, R Hal Scofield Grant/research support from: Pfizer, Xavier Mariette: None declared, Wan-fai Ng: None declared, Kathy L Sivils: None declared, Gunnel Nordmark: None declared, Betty Tsao: None declared, Christopher Lessard: None declared